2008
DOI: 10.2174/1875044300801010062
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film and Ocular Surface Surfactants

Abstract: The hydrophobic surfactant proteins B (SP-B) and C (SP-C) are tightly bound to phospholipids. These proteins play important roles in maintaining the surface tension-lowering properties of pulmonary surfactant. Surfactant protein A (SP-A) and D (SP-D) are extremely hydrophilic and are thought to have a role in recycling surfactant and especially in improving host defense in the lung. Moreover, SPA supports the hydrophobic surfactant proteins during surfactant subtype assembly and inhibits secretion of lamellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 68 publications
1
13
0
3
Order By: Relevance
“…These domains and the palmitoylation of the protein also support the hypothesis that SP-G may be integrated into and anchored within a lipid phase, as can be found within actual accepted models of the tear film [78], [79]. Our calculations showed that SP-G is able to reside in vicinity of lipid systems and may also interact with them.…”
Section: Discussionsupporting
confidence: 85%
“…These domains and the palmitoylation of the protein also support the hypothesis that SP-G may be integrated into and anchored within a lipid phase, as can be found within actual accepted models of the tear film [78], [79]. Our calculations showed that SP-G is able to reside in vicinity of lipid systems and may also interact with them.…”
Section: Discussionsupporting
confidence: 85%
“…As saliva plays an important role in maintaining the health of the oral cavity, an immunological function of the detected surfactant proteins SP-A and SP-D, well known from lung and other mucosal surfaces (for review see Bräuer and Paulsen 2008), is not astonishing. In this context, Lee et al (2005) demonstrated that SP-A is up-regulated in forms of chronic sialadenitis, which is caused by microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…In innate host defense, ANG is a component of tears and protects the ocular surface as an antimicrobial peptide [114,115]. ANG is also abundantly induced in Paneth cells and has been demonstrated to act as a factor for innate antimicrobial defense of the intestine [13].…”
Section: Ang Participates In Immune Responsesmentioning
confidence: 99%